A long-term controlled release of the drug for osteoporosis from the surface of titanium implants coated with calcium zeolite. (18th June 2021) - Sandomierski, Mariusz; Zielińska, Monika; Voelkel, Adam
Abstract : The aim of this study was to prepare an implant material enabling a slow, gradual and gentle release of risedronate. Abstract : The aim of this study was to prepare an implant material enabling a slow, gradual and gentle release of risedronate. Such material was designed to allow the sorption of a large quantity of risedronate, and then enable the controlled and long-term release in minimal doses over many years. To achieve this goal, titanium implants coated with calcium zeolite were prepared. Successive release of risedronate at a low level was ensured as a result of ion exchange under the influence of a constantly flowing medium, which was a simulated body fluid. Titanium modifications, as well as sorption and desorption processes, were confirmed using a variety of methods: XRD, FTIR, SEM, EDS and XPS (to determine surface modification and risedronate sorption), and UV-VIS spectroscopy (to determine drug sorption and release profile). Based on the obtained results, it can be concluded that the proposed solution will allow for the preparation of endoprostheses dedicated to patients with bone diseases such as osteoporosis.